Contextual Learning Model for Indonesian Language Based on Tourism Literature - Moh. Zainudin (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Learning Indonesian language is not only focus on aspects linguistic , but also has role strategic in planting values culture , history , and wisdom local . Article This study in a way conceptual integration of tourism literature to in Indonesian language learning based on contextual , with lift potential destination history in Mojokerto Regency . Approach This believed capable increase competence literacy student at a time grow awareness will inheritance culture local . With referring to the theory constructivism , approach learning based tourism literary texts , as well as implementation context local in learning , articles This serve framework relevant conceptual and development models For applied at all levels medium and college tall.